Review of the Research Program of the U.S. DRIVE Partnership : fourth report (National Academies Press, 2013)
This report by the National Research Council's (NRC's) Committee on Review of the U.S. DRIVE Research Program, Phase 4, follows three previous NRC reviews of the FreedomCAR and Fuel Partnership, which was the predecessor of the U.S. DRIVE Partnership (NRC, 2005, 2008a, 2010). The U.S. DRIVE (Driving Research and Innovation for Vehicle Efficiency and Energy Sustainability) vision, according to the charter of the Partnership, is this: "American consumers have a broad range of affordable personal transportation choices that reduce petroleum consumption and significantly reduce harmful emissions from the transportation sector."--